Biocomposite boards from wheat straw without addition of bonding agent. (May 2014) - Zhao, L.; Xia, W.; Tarverdi, K.; Song, J.
<x content-type="archive" xml:space="preserve">Abstract</x> The present paper reports work in development of biocomposite boards compression moulded from wheat straw. Unlike most traditional wood based fibre/chip boards with addition of adhesives or bonding agents, attempt was made to utilise the lignin–hemicellulosic natural resin within straw as bonding agent, resulting in a class of 'binderless' and more natural biocomposite boards. The effects of straw preparation and compression moulding conditions on structural and mechanical properties of the binderless straw boards were studied systematically in terms of size of chopped straw, pretreatment and the combination of pressure and temperature during compression moulding. The bonding mechanisms of the natural resin in the straw biocomposites were investigated in terms of its mobilisation using NaOH pretreatment of straw and its redistribution to the straw interfaces during compression moulding process. Without any fractionation of straw or any additional adhesive bonding agent, the mechanical properties of the binderless straw boards were comparable to some commercially available wood and straw board products using addition of adhesives.